2010
DOI: 10.1097/cpm.0b013e3181fa13b5
|View full text |Cite
|
Sign up to set email alerts
|

Can We Translate Our Understanding of the Pathogenic Mechanisms of Silicosis Into a Therapeutic Plan?

Abstract: Over the last half century, there has been a sustained decline in the prevalence of silicosis in developed countries. This success has primarily been the result of an emphasis on engineering controls, with the capture of generated silica dust. This has allowed for adherence to exposure limits and the protection of the respiratory health of the worker. Yet sporadic cases continue to occur in developed countries and epidemics are still recognized in underdeveloped countries.In this review, we address data descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…11 Th e Chicago Initiative to Raise Asthma Health Equity (CHIRAH) study, in a sample of children 8 to 14 years old, found that having a detectable salivary cotinine level was associated with increased risk for asthma exacerbation. 12 Population-based studies have shown that adoption and implementation of smoke-free legislation reduces asthma hospitalization rates for children. 13 Although gestation is a particularly vulnerable time for pulmonary development, the eff ects of tobacco smoke exposure on respiratory problems of children continue well beyond birth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Th e Chicago Initiative to Raise Asthma Health Equity (CHIRAH) study, in a sample of children 8 to 14 years old, found that having a detectable salivary cotinine level was associated with increased risk for asthma exacerbation. 12 Population-based studies have shown that adoption and implementation of smoke-free legislation reduces asthma hospitalization rates for children. 13 Although gestation is a particularly vulnerable time for pulmonary development, the eff ects of tobacco smoke exposure on respiratory problems of children continue well beyond birth.…”
mentioning
confidence: 99%
“…Of course, the physician who prescribes these therapies must recognize that they lessen immunity and may predispose to infection. 12 Even if eff ective therapies can be developed, they will not serve as a replacement for limiting exposures, including removal of affected individuals from additional exposure.…”
mentioning
confidence: 99%